Favoring D2-Lymphadenectomy in Gastric Cancer - Karavokyros, Ioannis; Michalinos, Adamantios (Frontiers in Surgery, 2018)
The role of extended lymphadenectomy in the surgical treatment of gastric cancer has been debated for many years. So far six prospective randomized trials and a number of meta-analyses comparing D1- to D2-lymphadenectomy in open surgery have been published with contradicting results. The possible oncologic benefit of radical lymphadenectomy has been blurred by a number of reasons. In most of the trials the strategies under comparison were made similar after protocol violations. Imperfect design of the trials could not exclude the influence of cofounding factors. Inappropriate endpoints could not detect evidently the difference between the two surgical strategies. On the other hand radical lymphadenectomy was characterized by increased morbidity and mortality. This was mostly caused by the addition of pancreatico-splenectomy in all D2-dissections, even when not indicated. A careful analysis of the available evidence indicates that D2-lymphadenectomy performed by adequately trained surgeons without resection of the pancreas and/or spleen, unless otherwise indicated, decreases Gastric Cancer Related Deaths and increases Disease Specific Survival. This evidence is not compelling but cannot be ignored. D2-lymphadenectomy is nowadays considered to be the standard of care for resectable gastric cancer.